2007
DOI: 10.1097/mco.0b013e3282efdebb
|View full text |Cite
|
Sign up to set email alerts
|

Gut microflora as a target for energy and metabolic homeostasis

Abstract: Gut microflora may play an even more important role in maintaining human health than previously thought. The literature provides new evidence that the increased prevalence of obesity and type 2 diabetes cannot be attributed solely to changes in the human genome, nutritional habits, or reduction of physical activity in our daily lives. One must also consider this important new environmental factor, namely gut microbiota. Scientists may take into consideration a key question: could we manipulate the microbiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
1
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(224 citation statements)
references
References 44 publications
7
200
1
12
Order By: Relevance
“…Beneficial Bifidobacteria made the above four parts to become an interrelated whole (25). Our results were supported by previous published reports (4,25,32,34). The results of intestinal health were comparable with those from the traditional methods in the study.…”
Section: Analysis Of Intestinal Mucosal Immunitysupporting
confidence: 91%
See 2 more Smart Citations
“…Beneficial Bifidobacteria made the above four parts to become an interrelated whole (25). Our results were supported by previous published reports (4,25,32,34). The results of intestinal health were comparable with those from the traditional methods in the study.…”
Section: Analysis Of Intestinal Mucosal Immunitysupporting
confidence: 91%
“…In accordance with the mRNA analysis, compared with the control group, Lp-and Lp 590-fed improved the tight-junctions of rats (P \ 0.05), because the immunohistochemical staining of both proteins localized along the apical cellular border was greater with Lp and Lp 590 treatment compared with PBS treatment. Previous studies on the relationship between intestinal beneficial bacteria and permeability illustrated that Bifidobacteria can augment two proteins of ZO-1 and occludin and then promote gut permeability (34). The tendency also appeared in this study.…”
Section: Analysis Of Microbiota Metabolitessupporting
confidence: 77%
See 1 more Smart Citation
“…The imbalance between energy expenditure, caloric intake and energy storage, is known to contribute to the development of obesity (4). Recent studies have suggested that mechanisms not directly related to the human genome could be involved in the genesis of obesity, due to the fact that, when a determined population undergoes similar nutritional stress, not all individuals become hyperglycemic or present diet-related weight gain (5)(6)(7).…”
mentioning
confidence: 99%
“…The intestinal flora genome has approximately 100 times more genes than the human genome (5,9). Normal intestinal flora presents different functions that contribute to the functioning of our organism, therefore this flora can be considered a microbial organ (10,11).…”
mentioning
confidence: 99%